A copper–amyloid-β targeted fluorescent chelator as a potential theranostic agent for Alzheimer's disease. Issue 12 (19th October 2016) - Yang, Tao; Yang, Liu; Zhang, Changli; Wang, Yanqing; Ma, Xiang; Wang, Kun; Luo, Jian; Yao, Cheng; Wang, Xiaoyong; Wang, Xiaohui
Abstract : A fluorescent chelator is able to specifically target and attenuate Cu 2+ –Aβ aggregates in the brain of mice with Alzheimer's disease, which can be visualized by fluorescence imaging of the chelator. Abstract : Alzheimer's disease (AD) is a neurodegenerative disease and is still incurable. Traditional therapies use diagnostic and therapeutic drugs separately, which is unfavourable for exploring the pathology of AD and optimizing the efficacy of drugs. Theranostic agents that combine diagnosis and targeted therapy could overcome the weakness of current approaches through the complementary action between the two functions. Owing to the intense relevance to AD pathogenesis, metal-associated amyloid-β (Aβ) species have been considered as the primary targets for anti-AD. We herein report a fluorescent chelator (BTTA) as a potential theranostic agent for both attenuating and fluorescence imaging of Cu 2+ -induced Aβ aggregation in the AD brain. Considerable evidence shows that BTTA is able to specifically target Cu 2+ -associated Aβ aggregates and capture Cu 2+ ions to attenuate the aggregates and their neurotoxicity. Most notably, the disaggregation of Cu 2+ –Aβ aggregates can be monitored by the fluorescence changes of BTTA from both buffer and brain homogenates of AD mice. Moreover, BTTA can also be used to visually detect the Aβ aggregates via fluorescence imaging of slices of brain tissues from AD mice and is verified to penetrate the blood brain barrier of mice in vivo . These findings suggest that BTTA would provide a promising strategy to develop potential theranostic tools for AD.